Waqf scheme for government expenditure - Mohammad Ali Nasr, Wafa; Hasan, Aznan; Ibrahim Atah, Ummi (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
Purpose: The ultimate aim of this paper is to explore the possibility for the government to allow tax payers to select preferable social sector from the government expenditure that match Waqf principles, and the possibility for tax payers to delegate the management of the fund to the discretion of the government as the Waqf Mutawallee. Design/methodology/approach: Qualitative method suits best for this study as it mainly depends on conducting library research and deeply analysing and reviewing the literature. Finding: In Malaysia, the social sector is accounted for almost 38% of total government expenditure. This figure represents the largest beneficiary of the government allocation. Education, training and health subsectors are the main recipient sectors. At the same time, the Islamic charitable endowment scheme (Waqf) can be utilised for any Shariah compliant purpose whether in the form of economic assets that generate income such as farms, shops and shares, or social purposes such as the construction and managements of schools, hospitals and masjids. As Malaysia has succeeded in many aspects in the Islamic Financial Services Industry (IFSI) particularly in introducing the concept of tax rebate for zakat payment, Malaysia may also succeed in Waqf as well by introducing the policy which allows tax payers to select preferable social sectors from government expenditure which match the principle of waqf. The tax payers can choose his preference into which his tax payment will be channelled to. This scheme can be applied to all tax payers disregarding their religions as the beneficiaries under waqf may include Muslims as well as non-Muslims in the broader community. This research will investigate the relationship between the scope of Waqf in Shariah and the government expenditure in order to examine the ability of each item in the government expenditure to be included in Waqf criteria. It has been ever argued by early Muslim scholars that Zakat is the only financial due in Islam. Waqf, on the other hand, though not obligatory as zakat, played a significant role throughout the Muslims’ history as the capital gift or benevolent loan from the public to Allah for the benefit of the larger society. Introducing the concept of Waqf to the government expenditure will allow all tax payers to contribute to Waqf and to the Muslim, to enjoy the promised infinite reward from Allah via Waqf instead of it being a privilege exclusive to wealthy people, and at the same time enjoy the tax rebate. Originality/value: This study introduces a new connectivity between Waqf, Tax and Government Expenditure.